PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN: (Studi pada Perumda Tirta Terubuk Kabupaten Bengkalis) - Fairuz Jelita; Kartini Harahap; Onan Marakali Siregar (Transpublika Publisher, 2024)
In maintaining the sustainability of the company, human resources play a very important role. Therefore, the company needs to provide support to employees so that they feel valued, which will ultimately have a positive impact on their development and performance. This study aims to identify the influence of interpersonal communication and organizational support on employee performance at Tirta Terubuk Company in Bengkalis Regency. The results of this study indicate that Perceived Organizational Support partially affects Employee Performance, with a t-value of 3.220 > 1.6779 and a significance level of 0.039 < 0.05, as well as a positive regression coefficient value of 0.075. Interpersonal Communication partially affects Employee Performance with a t-value of 2.823 > 1.6779 and a significance level of 0.015 < 0.05, along with a positive regression coefficient value of 0.190. In simultaneous testing, Perceived Organizational Support and Interpersonal Communication have a simultaneous effect on employee performance variables of 65%, while the remaining 35% is influenced by other factors.